2004
DOI: 10.1007/s00408-004-2512-5
|View full text |Cite
|
Sign up to set email alerts
|

Drotrecogin Alfa (activated) Prevents Smoke-Induced Increases in Pulmonary Microvascular Permeability and Proinflammatory Cytokine IL-1β in Rats

Abstract: In an established rat model of smoke inhalation injury, we conducted a dose-response study to examine the protective effects of Xigris [drotrecogin alfa (activated) (DrotAA)], a recombinant form of human activated protein C (APC). DrotAA is a serine protease (approximately 55 kD molecular weight) with the same amino acid sequence and the glycosylation site as human plasma-derived APC. A total of 120 F344/NH rats (half each gender, approximately 175 g body weight) were randomly divided into five groups and expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Mizutani et al [22] reported that intravenous administration of 100 mg/kg activated protein C significantly inhibited ischemia-reperfusioninduced increases in renal levels of TNF-a in rats. On the other hand, Wong et al [21] did not observe decrease in bronchoalveolar lavage fluid TNF-a levels with activated protein C doses of 5, 10 and 20 mg/kg. In the present study, 2 mg/kg/h activated protein C was infused intravenously, as the regimen with 2 mg/kg activated protein C intravenous bolus injection was reported to be protective in ischemic brain cells.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mizutani et al [22] reported that intravenous administration of 100 mg/kg activated protein C significantly inhibited ischemia-reperfusioninduced increases in renal levels of TNF-a in rats. On the other hand, Wong et al [21] did not observe decrease in bronchoalveolar lavage fluid TNF-a levels with activated protein C doses of 5, 10 and 20 mg/kg. In the present study, 2 mg/kg/h activated protein C was infused intravenously, as the regimen with 2 mg/kg activated protein C intravenous bolus injection was reported to be protective in ischemic brain cells.…”
Section: Discussionmentioning
confidence: 95%
“…Activated protein C has been shown to inhibit the generation of TNF-a in several studies [20]. Few studies, however, failed to demonstrate a decrease in TNF-a level after administration of activated protein C [21]. This may be partly due to the wide dose range of activated protein C used in different trials.…”
Section: Discussionmentioning
confidence: 98%
“…In rats, an intravenous dose of 100 g/kg, 2 mg/kg, or 20 mg/kg of APC, respectively, was found to prevent endotoxin-induced hypotension (52), ischemic stroke (53), or smoke-induced increases in pulmonary microvascular permeability and proinflammatory cytokine IL-1␤ (54). In the present results, a bolus injection of APC (0.5, 5, or 20 mg/kg, intravenously) significantly improved survival during heat stroke in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Higher doses increased airway resistance and tissue elastance, possibly by inducing bronchoconstriction. Increases in airway resistance with APC have also been described with intravenous injection in rats [38], although data in humans are lacking. At the doses chosen the aforementioned phenomena were not observed and no effects on other important outcomes such as lung histology or mechanics could be documented by APC administration in lungs ventilated with protective Vts [see Figure S2 in Additional file 1].…”
Section: Lvt-30minmentioning
confidence: 99%